PHYSICAL ACTIVITY PROFILE BASED ON GLOBAL PHYSICAL ACTIVITY QUESTIONNAIRE (GPAQ) FOR MINING WORKERS - Leonardo Lubis; Talia Rahmaniar; Nandina Oktavia (The Indonesian Journal of Public Health, 2023)
Introduction: Physical activity has several related factors, which are age, gender, educational level, and type of occupation. It is known that 1 in 4 adults in the world do not meet the minimum physical activity. Physical inactivity is one of the main factors causing non-communicable disease (NCD) as well as obesity, heart disease, and cancer. In Indonesia, 26.1% of the population is included in the category of less physical activity. Aims: to find out the physical activity profile of mining workers based on age, gender, educational level, and type of occupation. Methods: This study uses a descriptive design study with a cross-sectional approach that included 124 workers at PT. Borneo Indobara 2020. The measure was used in this research is the Global Physical Activity Questionnaire (GPAQ). The total level of physical activity is divided into three categories in MET-minutes/week, which are high (≥ 3.000 MET), moderate (≥ 600 or < 3.000 MET), and low (< 600 MET). Result: The workers who have a higher percentage of low physical activity are workers of middle age, female, highly educated, and have a position as leader/officer which is 75% compared to each category. Conclusion: The majority of mining workers at PT. Borneo Indobara has low physical activity. This research can be used as feedback or consideration for evaluating and motivating mining workers at PT. Borneo Indobara and the wider community to increase physical activity.